2011
DOI: 10.1348/174866410x497382
|View full text |Cite
|
Sign up to set email alerts
|

The role of encoding strategies in the verbal memory performance in patients with schizophrenia

Abstract: BACKGROUND. Verbal learning and memory is often compromised in patients with schizophrenia who prefer encoding words in order of their presentation (serial clustering) rather than using semantic categories (semantic clustering). METHOD. One hundred and four in-patients with schizophrenia were assessed twice with the California Verbal Learning Test. RESULTS. Patients showed significantly less semantic than serial clustering at both assessment times. Usage of encoding strategies were not stable over time. An inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Some studies have found that encoding is predominantly impaired. Superficial encoding (like serial encoding) is used more often by patients [51], but it is used less effectively than in healthy subjects [32,52]. Recourse to a semantic encoding strategy (also called deep encoding) is often a predictor of verbal learning capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that encoding is predominantly impaired. Superficial encoding (like serial encoding) is used more often by patients [51], but it is used less effectively than in healthy subjects [32,52]. Recourse to a semantic encoding strategy (also called deep encoding) is often a predictor of verbal learning capacity.…”
Section: Discussionmentioning
confidence: 99%
“…However, forced use of deep encoding strategies can help patients improve [4,5,32,42,52,53,54]. Thus, it might be helpful to teach remediation techniques that concentrate on practicing the choice of these semantic encoding strategies [51,55]. …”
Section: Discussionmentioning
confidence: 99%
“…Significant gains in insight may result by focusing cognitive remediation on memory training tasks and episodic encoding strategies. Interestingly, Fiszdon and colleagues 63 and Gsottschneider and colleagues 64 showed the effectiveness of such training for improving memory performance in patients with schizophrenia. Moreover, a recent study 60 has shown that improvement of insight and selfawareness in cognitive behaviour therapy is associated with increased precuneus activation during distorted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, successful episodic memory also depends upon processing semantic relationships between items, and there is evidence that relational memory processes are disproportionately impaired in SZ (Clare et al, 1993; Lepage et al, 2006; Ranganath, Minzenberg & Ragland, 2008; Titone et al, 2004). For example, on list-learning tasks such as the California Verbal Learning Test (CVLT; Delis et al, 1987; 2000), clustering of semantically-related words improves recall in healthy participants (Delis et al, 1987; 2000), but patients tend to rely on serial order (Gsottschneider et al, 2011) rather than semantic-clustering strategies, contributing to severe list-learning impairments (Brebion et al, 2004; Iddon et al, 1998; Stone et al, 1998). …”
Section: Introductionmentioning
confidence: 99%